2000
DOI: 10.1109/94.891999
|View full text |Cite
|
Sign up to set email alerts
|

Ozone production using pulsed dielectric barrier discharge in oxygen

Abstract: The production of ozone was investigated using a dielectric barrier discharge in oxygen, and employing short-duration pulsed power. The dependence of the ozone concentration (parts per million, ppm) and ozone production yield (g(O3)lkWh) on the peak pulsed voltage (17.5 to 57.9 kV) and the pulse repetition rate (25 to 400 pulsesls, pps) was investigated. In the present study, the following parameters were kept constant: a pressure of 1.01~10~ Pa, a temperature of 26 k 4T, a gas flow rate of 3.0 llmin and a gas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
42
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 25 publications
0
42
0
Order By: Relevance
“…Ohe et al [7] obtained a 110 g/kWh ozone yield in a thin-gap volume barrier discharge using a time-modulated power supply and reported more than a 20% improvement compared with a conventional continuous wave power supply. Samaranayake et al [8] investigated ozone production using a volume DBD in oxygen (gaseous gap 11 mm) employing short-duration pulsed power, and varying the peak pulse voltage and pulse repetition rate at a fixed oxygen flow (3 slm). The highest production yield of ozone (202 g/kWh) with an ozone concentration of 4-5 9 10 3 ppm (*8-10 g/m 3 ) was achieved at the lowest applied pulse repetition rate.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Ohe et al [7] obtained a 110 g/kWh ozone yield in a thin-gap volume barrier discharge using a time-modulated power supply and reported more than a 20% improvement compared with a conventional continuous wave power supply. Samaranayake et al [8] investigated ozone production using a volume DBD in oxygen (gaseous gap 11 mm) employing short-duration pulsed power, and varying the peak pulse voltage and pulse repetition rate at a fixed oxygen flow (3 slm). The highest production yield of ozone (202 g/kWh) with an ozone concentration of 4-5 9 10 3 ppm (*8-10 g/m 3 ) was achieved at the lowest applied pulse repetition rate.…”
mentioning
confidence: 99%
“…Ozone generation efficiency has been widely studied in laboratory conditions and performance has been reported for systems based on pulsed corona discharges and various dielectric barrier discharges [4][5][6][7][8][9][10][11]. For example, more than 20 years ago, Masuda et al [4] reported a surface continuously AC excited (10 kHz and 10 kV peak-to-peak) dielectric barrier discharge (DBD) ozoniser based on a high-purity alumina ceramic with parallel strip-like discharge electrodes and a grounded water-cooled film-like induction electrode capable of producing ozone concentration as high as 5-10 9 10 4 ppm.…”
mentioning
confidence: 99%
“…Figure 14 shows that the pulse repetition rate does not influence strongly the production yield. Above about 39 kV, the input energy per pulse increases with increasing voltage at a faster rate than linearly while the concentration of ozone increases linearly [26]. This results in the reduction of the yield with further increasing voltage.…”
Section: Ozone Production In a Reactor With A Pvc Dielectric Barrier mentioning
confidence: 98%
“…The presence of the dielectric layer is very useful, as it enables the application of a higher pulsed voltage to the reactor before a breakdown of the gap occurs. Therefore, a larger amount of energy can be fed into the discharge resulting in a higher production of ozone [26].…”
Section: Ozone Production Using Different Gaseous Gap Lengths In a Rementioning
confidence: 99%
“…The dielectric material forms a barrier, which hinders the development of the arc discharge and the breakdown of the gas flowing into the gap (Peeters et al, 2016). In the case of DBD using O 2 as gas source, electrons dissociate the oxygen molecules into atoms that, through three-body reactions, generate O 3 species (Samaranayake et al, 2000).…”
Section: Evaluation Of Disposable Medical Device Packaging Materials mentioning
confidence: 99%